2017
DOI: 10.1088/2058-6272/19/2/025502
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results ofin situlaser-induced breakdown spectroscopy for the first wall diagnostics on EAST

Abstract: Preliminary results of in situ laser-induced breakdown spectroscopy for the first wall diagnostics on EAST * Zhenhua HU (胡振华) 1 , Cong LI (李聪) 2 , Qingmei XIAO (肖青梅) 2 , Ping LIU (刘平) 2 , Fang DING (丁芳) 1 , Hongmin MAO (毛红敏) 1 , Jing WU (吴婧) 1 , Dongye ZHAO (赵栋烨) 2 , Hongbin DING (丁洪斌) 2 , Guang-Nan LUO (罗广南) 1 and EAST team

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Approximately, a 7.0 lm thick lithium film (0.534 g cm À3 , 300 K) was deposited on the wall, as directly evidenced by the laser-induced breakdown spectroscopy system measurement. 20 At this level of wall conditioning, no obvious change in the L-H power threshold can be observed with respect to lithium accumulation in this experiment. This result is in agreement with the previous experiments, 21 where strong effects on the L-H power threshold have been observed in the Mo/C wall due to heavy lithium-wall coating, over 800 g. The experiment in the effect of the rB drift direction on the L-H transition was carried out under comparable levels ($200 g) of lithium conditioning, as also evidenced by the similar intensity level of line emission from lithium (see Fig.…”
Section: Methodsmentioning
confidence: 53%
“…Approximately, a 7.0 lm thick lithium film (0.534 g cm À3 , 300 K) was deposited on the wall, as directly evidenced by the laser-induced breakdown spectroscopy system measurement. 20 At this level of wall conditioning, no obvious change in the L-H power threshold can be observed with respect to lithium accumulation in this experiment. This result is in agreement with the previous experiments, 21 where strong effects on the L-H power threshold have been observed in the Mo/C wall due to heavy lithium-wall coating, over 800 g. The experiment in the effect of the rB drift direction on the L-H transition was carried out under comparable levels ($200 g) of lithium conditioning, as also evidenced by the similar intensity level of line emission from lithium (see Fig.…”
Section: Methodsmentioning
confidence: 53%
“…These values of η and χ are quite low. Figure 7 also reports the temperature-dependent neutral and ionic densities evolution based on the composition (11). For most species in the present conditions, the temperature interval [8 000, 12 000] K corresponds to the balance from neutrals to ions, except for C, N and O due to their ionization potential.…”
Section: Plasma Composition Determination Proceduresmentioning
confidence: 96%
“…The in situ LIBS analysis of EAST (Experimental Advanced Superconducting Tokamak) walls have been performed some years ago by Hu et al [10,11]. More recently, Almaviva et al have developped a remote-LIBS facility to analyze FTU (Frascati Tokamak Upgrade) PFUs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of the light emitted from the plasma plume is used to determine the elemental composition of the ablated material. It has been demonstrated that LIBS can be used for remote in-situ determination of the hydrogen isotopes in the W based materials both in tokamaks [14][15][16][17] and linear plasma devices [18][19][20][21][22]. The determination of the absolute value of D content requires extensive calibration with different coatings.…”
Section: Introductionmentioning
confidence: 99%